Eficácia do swap cambial nas intervenções intraday do Banco Central, como redutor da volatilidade nas negociações no mercado futuro de câmbio - Sales, Aparecido Francisco de (2019)
One of the most important components of the economy is the price of foreign currency, in this case the dollar. The control of volatility and price level, essential to avoid economic turbulence, almost obliges the monetary authority to intervene in the foreign exchange market. The foreign exchange swap, a widely used derivative in Brazil, is an instrument that allows sterilized interventions, with no impact on liquidity. The study identified, on the basis of high frequency data analysis of the future dollar market, the impact that the Exchange Swap auctions provoke on business volatility in the future foreign exchange market, the difference of reaction to the scheduled auctions and surprise, to rollovers or offers of new maturities. Numerous studies are inconclusive, given the method, period and / or applied tests. The ARCH-GARCH models were used to identify the level of volatility in each adjacent period to each auction. The quantification of periods with the increase volatility indicates that the interventions of Central Bank through Currency Swaps have little effectiveness in reducing the volatility in the trades made in the future foreign exchange market, standard contracts - DOL and mini-contracts - WDO, especially during ten minutes of the auction. On the other hand, the auctions to offer new maturities, scheduled or not, increase the volatility in a significant number of trading sessions, especially in the ten minutes after the auction.